2011
DOI: 10.1021/jp200310b
|View full text |Cite
|
Sign up to set email alerts
|

Complex Analysis of the Aluminum Siting in the Framework of Silicon-Rich Zeolites. A Case Study on Ferrierites

Abstract: We present a multistep method combining multispectroscopic experiments with DFT calculations to determine the complete Al distribution in silicon-rich zeolites, independent of the presence of AlÀOÀ(SiÀO) n ÀAl (n = 1, 2) sequences in their frameworks. 29 Si MAS NMR spectroscopy is employed to confirm the absence of AlÀOÀSiÀOÀAl in the framework of silicon-rich zeolites while 27 Al 3Q MAS NMR spectroscopy and DFT computations of 27 Al isotropic chemical shifts serve to determine the locations of isolated Al ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(163 citation statements)
references
References 69 publications
7
156
0
Order By: Relevance
“…The Al4-O-(SiO) 2 -Al4 site has the lowest S E (Si/Al), suggesting the most stable configuration of Brönsted acid formation in the 2-Al substitution models. Herein the Al4-O-(SiO) 2 -Al4 sequence is located in one 6-membered ring; the experiments carried out by Dedecek and his co-workers [23] identified the locations of the Al-O-(SiO) 2 -Al in a ring, which is excellently consistent with our result. The Al1-O-(SiO) n -Al4 (n = 2, 3) configurations have a similar S E (Al/Si) of around 15 kcal/mol, indicating that the stability exhibits little dependency on the number of SiO groups between the two Al sites.…”
Section: N-al Substitution (N ≥ 2)supporting
confidence: 91%
See 1 more Smart Citation
“…The Al4-O-(SiO) 2 -Al4 site has the lowest S E (Si/Al), suggesting the most stable configuration of Brönsted acid formation in the 2-Al substitution models. Herein the Al4-O-(SiO) 2 -Al4 sequence is located in one 6-membered ring; the experiments carried out by Dedecek and his co-workers [23] identified the locations of the Al-O-(SiO) 2 -Al in a ring, which is excellently consistent with our result. The Al1-O-(SiO) n -Al4 (n = 2, 3) configurations have a similar S E (Al/Si) of around 15 kcal/mol, indicating that the stability exhibits little dependency on the number of SiO groups between the two Al sites.…”
Section: N-al Substitution (N ≥ 2)supporting
confidence: 91%
“…Therefore it is necessary to study the distribution of different amount of Al atoms and the acid strength of Brönsted acid sites in FER zeolite. Although the experiment research on these issues was mentioned a little, several DFT calculations were also carried out to investigate the distribution of Al in FER zeolite [23,24]. However their cluster model was so extremely small that it could not represent the various types of Al/Si distributions, which are believed to be significant in determining the catalytic reactivity in butene isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…The first two models (a and bÀ2) represent isolated cationic sites while the other two models (bÀ1 + bÀ1 and bÀ2 + bÀ2) feature two cooperating adjacent Fe II cationic sites. [9]) revealed that bÀ2 and a cationic sites are present in the sample. Moreover, our recent study [9] of the parent ferrierite zeolite (FER/D in ref.…”
Section: Structural Modelsmentioning
confidence: 98%
“…[7] The four models, possessing P1 symmetry, were utilized to investigate four distinct possible arrangements of the active sites in ferrierite. Moreover, our recent study [9] of the parent ferrierite zeolite (FER/D in ref. The bÀ1 model was not used in this study since N 2 O does not adsorb via the O atom on Fe II accommodated in isolated bÀ1 sites, [7] and therefore, no isotope exchange can occur.…”
Section: Structural Modelsmentioning
confidence: 99%
“…The Al siting in the zeolite frameworks [i.e., the crystallographically distinguishable tetrahedral (T) sites that are occupied by Al] was clearly shown to be neither random nor controlled by simple rules, but to depend on the conditions of their hydrothermal synthesis . This means that Al atoms can be located in zeolites of the same topology and Al concentration at various crystallographically distinguishable T sites ,,,. Therefore, obtaining insights into the Al locations in the channel system of ZSM‐5 is of crucial importance for development of highly selective catalysts.…”
Section: Figurementioning
confidence: 99%